Optimization of Cervical and Ocular Vestibular Evoked Myogenic Potential Testing Using an Impulse Hammer in Adults, Adolescents, and Children - Rodriguez, Amanda I. (Otol Neurotol, 2020)
OBJECTIVE: To characterize cervical and ocular vestibular evoked myogenic potential (c- and oVEMP) responses using an impulse hammer (IH) in adults and pediatrics at standardized force levels and evaluate: the relationship of force level on VEMP amplitude, sternocleidomastoid (SCM) contraction on cVEMP amplitude, required number of tap stimuli, and subject comfort. Using these data, optimal testing parameters were selected. STUDY DESIGN: Prospective study. SETTING: Tertiary referral center. PATIENTS: Seventy- eight healthy adults, adolescents, and children with no hearing or vestibular deficits. INTERVENTIONS: All subjects received c- and oVEMP testing using IH and 500 Hz tone burst air conduction stimuli. Adults received hard, medium, and soft force levels. Adolescents and children received medium and soft force levels. A comfort questionnaire was administered pre- and post-testing. MAIN OUTCOME MEASURES: IH VEMP response parameters (response rates, latency, cVEMP pre-stimulus SCM EMG, and peak-to-peak amplitude) were assessed per force level. Subjective reporting for patient comfort was also assessed. RESULTS: VEMP response rates ranged from to 92 – 100%. Force had a linear relationship with VEMP amplitude. SCM contraction had a linear relationship with raw cVEMP amplitude; however, dissipated with amplitude normalization. Force level did not impact the number of taps needed. A minimum peak force of 15 – 20 N, accounting for SCM contraction, and using a lower EMG monitoring limit for cVEMP is recommended to elicit reliable responses. CONCLUSIONS: Overall, IH VEMP is appropriate and comfortable to use in adults and pediatrics and can be useful when an air conduction stimulus is contraindicated or not preferred.